(3OjhGf GdWZQGFjs - (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3cJH GdCLd Edi HYV ef CdJeS efg CTYGQg(B: (3bO EfJgjJ Edi eG GbJQMg GdTjN GdEeGe COGe Gddg fYeJg hCKHJ WQakG eeG Jdb HMaXj s
(3BNQgG (B:s
(3Ndjdj EeG Cf JYjfG hJSYOG hEeG caGakG dG Ydi hdG djG s
(3fSNI SGOSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B148 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B798s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdQjWGfj (B(1558) s
Keywords: (3GdCOHs